A Strain-Driven Antiferroelectric-to-Ferroelectric Phase Transition in La-Doped BiFeO3 Thin Films on Si - Chen, Deyang; Nelson, Christopher T.; Zhu, Xiaohong; Serrao, Claudy R.; Clarkson, James D.; Wang, Zhe; Gao, Ya; Hsu, Shang-Lin; Dedon, Liv R.; Chen, Zuhuang; Yi, Di; Liu, Heng-Jui; et al. (My University, 2017)
A strain-driven orthorhombic (O) to rhombohedral (R) phase transition is reported in La-doped BiFeO3 thin films on silicon substrates. Biaxial compressive epitaxial strain is found to stabilize the rhombohedral phase at La concentrations beyond the morphotropic phase boundary (MPB). By tailoring the residual strain with film thickness, we demonstrate a mixed O/R phase structure consisting of O phase domains measuring tens of nanometers wide within a predominant R phase matrix. A combination of piezoresponse force microscopy (PFM), transmission electron microscopy (TEM), polarization electric field hysteresis loop (P-E loop), and polarization maps reveal that the O-R structural change is an antiferroelectric to ferroelectric (AFE-FE) phase transition. Using scanning transmission electron microscopy (STEM), an atomically sharp O/R MPB is observed. Moreover, X-ray absorption spectra (XAS) and X-ray linear dichroism (XLD) measurements reveal a change in the antiferromagnetic axis orientation from out of plane (R-phaSe) to in plane (O-p hase). These findings provide direct evidence of spin-charge-lattice coupling in La-doped BiFeO3 thin films. Furthermore, this study opens a new pathway to drive the AFE-FE O-R phase transition and provides a route to study the O/R MPB in these films.
Keywords: BiFeO3; multiferroic; antiferroelectric; strain engineering; spin-charge-lattice coupling; antiferromagnetic